Economic shocks and clinging - Stan Veuger; Michael R. Strain (American Enterprise Institute (AEI), 2019)
Michael Strain and Stan Veuger find that the economic effects of globalization do indeed change the attitudes of whites toward immigrants, minorities, religion, and guns. More specifically, they find evidence of significant hardening of existing attitudes – that is, the impact of these import shocks appears concentrated in the tails of the distribution over attitudes.
Keywords: A; 330; Globalization; Working Paper